An efficient measure for the isolation of chenodeoxycholic acid from chicken biles using enzyme-assisted extraction and macroporous resins refining - Biao Yang; Fangyun Lu; Pengpeng Li; Jingjing Ma; Jing Yang; Xinxiao Zhang; Mei Cheng; Wenjing Yu; Yao Chai; Ye Zou; Weimin Xu; Daoying Wang (Poultry Science)
Chicken bile is a by-product of chicken processing, rich in chenodeoxycholic acid (CDCA), an active pharmaceutical raw material. In this study, a green measure for the extraction and purification of CDCA from chicken biles by enzymatic hydrolysis and macroporous resins refining was established. For the assisted extraction of CDCA, the active bile salt hydrolase (BSH) from Bifidobacterium was heterologously expressed and applied, its activities on GCDCA and TCDCA were 4.96 ± 0.32 U/mg and 3.07 ± 0.031 U/mg and optimal catalytic conditions for the extraction of CDCA were determined as 0.04 g/g of the enzyme dosage, pH 5.0 and 38 °C. Through validation of the conditions, the yield of CDCA was up to 5.32 %, which was equivalent to that by saponification method. In order to further refine CDCA from the extract obtained by enzyme-assisted extraction, a more preferable resin, AB-8 was selected for the purification of CDCA, which had a good adsorption capacity of 61.06 ± 0.57 mg/g for CDCA. Besides, the obtained CDCA extract was purified through AB-8 resin, the purity of CDCA was improved from 51.7 % to 91.4 % and the recovery yield of CDCA was 87.8 %. The advantages of energy conservation, time saving, economy and environmental friendliness make the measure using enzyme-assisted extraction and macroporous resins refining a promising candidate for isolation of CDCA from chicken bile.